(untitled) (Research, Society and Development, 2025)
The physiological and aesthetic changes during the gestational and postpartum periods highlight skin modifications, such as stretch marks and tissue laxity, which affect women’s self-esteem. During pregnancy, skin stretching and hormonal variations rupture collagen and elastin fibers, causing atrophic lesions and loss of elasticity. This study aimed to analyze post-gestational body effects and discuss the relevance of aesthetic and cosmetic approaches in restoring skin firmness and appearance. This is a qualitative, descriptive, and observational clinical case study that evaluated a 28-year-old mixed-race woman residing in Manaus-AM, in the postpartum period, with complaints of abdominal stretch marks and tissue laxity. Data collection occurred through anamnesis, physical examination, and photographic record, respecting ethical principles. White, linear, and atrophic stretch marks were observed in the gluteal and abdominal regions, associated with slight skin laxity and absence of inflammation. The patient maintained healthy habits, adequate hydration, and regular physical activity, but reported aesthetic discomfort and body dissatisfaction. Clinical analysis indicated mature alba stretch marks and mild laxity, resulting from tissue distension and incomplete dermal restructuring. The results highlight the importance of the aesthetic and cosmetic professional in the preventive and therapeutic guidance of these dysfunctions, even in the absence of direct intervention. It is concluded that such changes are common in the puerperium and require monitoring and encouragement of self-care, aiming to restore the physical and emotional well-being of the woman.